Qawwāmūn and Qawām in the Qur’an: A Romantic Semantic Analysis as a Response to Patriarchy - Mufti Abqary; Abd. Muid Nawawi; Nur Rofiah (PT. Student Rihlah Indonesia, 2026)
The interpretation of the term Qawwāmūn in Q. An-Nisā’ 4:34 has frequently been employed to justify patriarchal structures. The research gap addressed in this study lies in the predominance of normative-legalistic readings that insufficiently explore the semantic depth and literary nuance of the verse. This study aims to reconstruct the meaning of Qawwāmūn through the Romantic Semantic Tafsir (RST), an integrative exegetical model that combines Qur’anic semantic analysis with a romantic reading of divine discourse. Employing semantic analysis, this research traces all occurrences of Qawwāmūn (the mubālaghah form of ism al-fā‘il) and Qawām (the maṣdar form) in the Qur’an, which appear three times for Qawwāmūn (Q. An-Nisā’ 4:34; Q. An-Nisā’ 4:135; Q. Al-Mā’idah 5:8) and once for Qawām (Q. Al-Furqān 25:67). The findings reveal two core semantic principles underlying these terms: delegation and moderation. From the perspective of RST, the romantic divine message is articulated through emotional elements as drivers of ethical action and through freedom as liberation from oppressive patriarchal constraints. This study contributes a relational-ethical reinterpretation of Qawāmah, positioning men as delegates of justice (qiṣṭiyyah) and agents of moderation in gender relations.